Percutaneous Holmium Laser Fulguration of Calyceal Diverticula - Amjad Alwaal; Raed A. Azhar; Sero Andonian (Case Reports in Urology)
Introduction. Calyceal diverticular stones are uncommon findings that represent a challenge in their treatment, due to the technical difficulty in accessing the diverticulum, and the high risk of their recurrence. Current percutaneous technique for calyceal diverticular stones involves establishing a renal access, clearing the stone, and fulguration of the diverticular lining with a roller-ball cautery electrode using hypotonic irrigation solution such as sterile water or glycine solution which may be associated with the absorption of hypotonic fluids with its inherent electrolyte disturbances. Case Report. In this paper, we present for the first time percutaneous holmium laser fulguration of calyceal diverticula in 2 patients using normal saline. Their immediate postoperative sodium was unchanged and their follow-up imaging showed absence of stones. Both patients remain asymptomatic at 30 months post-operatively. Conclusion. This demonstrates that holmium laser is a safe alternative method to fulgurate the calyceal diverticulum after clearing the stone percutaneously.